The Role of CVP Analysis in Strategic Decision-Making for Small and Medium Enterprises - Joshi, Tirth Raj; Sapkota, Shiba Prasad (AMC Journal (Dhangadhi), 2026)
This paper explores the connections between Cost-Volume-Profit (CVP) analysis, profit planning and pricing decision-making in small and medium-sized enterprises (SMEs) in the Kailali district. Correlational and descriptive analysis using convenience sample of 193 respondents showed positive perception with regards to CVP analysis and its managerial practices with the highest mean scores of Applying CVP (M = 3.98), Profit Planning (M = 4.05), and Pricing Decision (M = 4.10) higher than the mean score of 3.0. Analysis of correlation showed that there was a strong, positive and significant relationship between the three constructs: applying CVP and Profit Planning (r = 0.829, p=0.00), Applying CVP and Pricing Decision (r = 0.787, p =0.00) and Profit Planning and Pricing Decision (r = 0.837, p=0.00). Profit planning and pricing decision jointly explained 71.6% of the variance in the application of CVP analysis (R² = 0.716, p=0.00). The high explanatory power and high correlations of the model are an indication that SMEs that apply CVP analysis are in a better position to make data-driven decisions, which enhance profitability, efficiency in the pricing and financial sustainability in the long run. These results affirm that CVP analysis is an important management tool that will increase profitability and pricing efficiency. The research concludes that the successful use of CVP analysis helps SMEs to make data-driven and informed decisions, enhancing financial performance, and leading to long-term sustainability.